La violenza nel rapporto uomo donna - Riggio, Martino; Fagioli, Luca; De Simoni, Enrica (Il sogno della farfalla, 2009)
After having highlighted the difficulties of defining the borders of what and to what extent in a relationship between a man and a woman is subject to falling ill, the authors discuss a dimension of violence which may be manifest and visible, in spite of the fact that it may not produce physical violence, that is to say it is violence of a psychic nature. They describe two pathological typologies, depression and schizoidia, and their characteristics and the way they are often interrelated. At the end, using a film as a clinical case, they hypothesize the possibility of a depressive breakdown which follows not only a violence experienced, but the violence produced by the mental activity of the depressed patient.